Diversity of movements by individual anadromous coastal cutthroat trout Oncorhynchus clarkii clarkii. Issue 5 (4th September 2013) - Goetz, F. A.; Baker, B.; Buehrens, T.; Quinn, T. P.
<x xml:space="preserve">Abstract</x> Wild, downstream‐migrating cutthroat trout, Oncorhynchus clarkii clarkii, smolts and adults were captured at a weir in Big Beef Creek, Hood Canal, Washington, surgically implanted with acoustic tags and tracked to identify spring and summer movements using stationary receivers in order to test the assumption that the species moves little while in marine waters. Overall, 93–96% migrated from the stream into the east side of the long narrow fjord, where they dispersed north and south along the shoreline. Most O. c. clarkii were detected nearshore within 10 km of the release site, with declining detection rates to 77 km. Over one‐third (36%) crossed c. 2–4 km of deep water to the other side but only one O. c. clarkii left the Hood Canal basin. Movements and behaviour patterns did not differ between smolts and adults but cluster analysis revealed two modes of distribution, here categorized as residents and migrants. Within these categories of overall distribution, a range of finer‐scale behaviour patterns was observed, including sedentary individuals, daily moving between proximate sites and more continuous long‐distance travel. Diel movement patterns varied markedly among individuals but overall activity increased near dawn, peaked around mid‐day and declined but continued at night. These patterns contrast with sympatric and closely related steelhead trout, Oncorhynchus mykiss, providing new insights into the diversity of salmonid behaviour.